Emerging Lessons from Half a Century of Fiscal Federalism in Switzerland - Kurt Schmidheiny (Swiss Journal of Economics and Statistics, 2017)
Over the last six years, researchers collaborating through the SNF Sinergia Project have collected data on fiscal federalism in Switzerland over more than half a century. The analysis of these new data in a range of projects has generated new and robust evidence on fiscal interdependencies among local governments and on behavioral responses of households facing local differences. This article presents some of the data collected and reports on nine examples of associated research projects.
Keywords: 330